AN ANALYSIS ON STUDENTS’ ERRORS IN DISTINGUISHING BETWEEN COLLECTIVE NOUN AND PLURAL NOUN - Samhudi (Getsempena English Education Journal, 2015)
This research was conducted to find out the students errors in distinguishing between collective and plural noun and the factors made the students errors in distinguishing between collective noun and plural noun. In collecting required data, the researcher used interview and test. The subject of this research was the students at class VII2 SMPN 1 Nisam which consisted of 29 students. The result of this research shown that the students errors were divided into three categories, namely, errors of omission, errors of addition and errors of misuse. Based on the result of test, it was found out that there were 10,7% of students made errors of omission, 67,4% errors of misuse and 21,9 % errors of addition. The result of interview shown that students made many errors caused by two factors; they are external and internal factor. External factor come from the method of teaching, because how well the students understand the material depends on the method of teaching that used by the teacher. Internal factor was the students themselves, they did not pay attention to their study, some of them were afraid and shy to ask the teacher if they do not understand the material. Some of them were did not do repetition of their lesson or lazy to study.